International westerns : re-locating the frontier (Scarecrow Press, Incorporated, 2014)
This collection of essays examines non-American Westerns and explores their significance, meanings, and reception. These essays also look at how Hollywood sensibilities are reflected, distorted, or challenged by filmmakers of Westerns in Europe, Australia, and other regions outside the U.S.